1979
DOI: 10.1128/jvi.32.2.557-566.1979
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of murine mammary tumor virus RNA expression during mammary tumorigenesis in BALB/c mice

Abstract: The effects of glucocorticoids and prolactin on murine mammary tumor virus (MuMTV) RNA expression in preneoplastic outgrowth lines and mammary tumors in BALB/c mice were investigated. Hyperplastic alveolar nodules (HAN) and a ductal hyperplasia (DH) are induced in virgin BALB/c mice by prolonged hormonal stimulation or treatment with 7,12-dimethylbenz(a)anthracene or both. Mice bearing HAN or DH outgrowth lines and mammary tumors that arose from the outgrowth lines were treated with glucocorticoids or prolacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
1

Year Published

1980
1980
1987
1987

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
1
1
1
Order By: Relevance
“…It should be noted, however, that our results discussed above contrast with the previous findings of Pauley et al (12,13) and Michalides et al (6, 7), which indicated that BALB/ c hormonally induced mammary tumors contain significantly greater quantities of MuMTV RNA than do normal lactating mammary glands. However, great variation in the quantity of MuMTV-related RNA has been found in cells obtained from BALB/c mammary tumors (12,13). Our data show that there is significant variation in the apparent amount of MuMTV-like RNA in both mammary glands and tumors, depending upon the method of extraction.…”
Section: Mumtv-related Rna In Mammary Tissuescontrasting
confidence: 96%
See 2 more Smart Citations
“…It should be noted, however, that our results discussed above contrast with the previous findings of Pauley et al (12,13) and Michalides et al (6, 7), which indicated that BALB/ c hormonally induced mammary tumors contain significantly greater quantities of MuMTV RNA than do normal lactating mammary glands. However, great variation in the quantity of MuMTV-related RNA has been found in cells obtained from BALB/c mammary tumors (12,13). Our data show that there is significant variation in the apparent amount of MuMTV-like RNA in both mammary glands and tumors, depending upon the method of extraction.…”
Section: Mumtv-related Rna In Mammary Tissuescontrasting
confidence: 96%
“…Furthermore, the quantity of MuMTV-related RNA, which was barely detectable when method 1 was used for extraction, was significantly increased if method 2 was used for obtaining RNA from mammary glands or tumors. This result suggests that the presence of RNase in both BALB/c mammary glands and tumors may have resulted in the failure to report measurable MuMTVrelated RNA levels by investigators using procedures similar to method 1 (1,2,6,7,12,13,20). Our results are in general agreement with those of Michalides et al (6, 7), Dudley et al…”
Section: Mumtv-related Rna In Mammary Tissuessupporting
confidence: 91%
See 1 more Smart Citation